Viral gut metagenomics of sympatric wild and domestic canids, and monitoring of viruses: Insights from an endangered wolf population. Issue 12 (27th April 2017) - Conceição‐Neto, Nádia; Godinho, Raquel; Álvares, Francisco; Yinda, Claude K.; Deboutte, Ward; Zeller, Mark; Laenen, Lies; Heylen, Elisabeth; Roque, Sara; Petrucci‐Fonseca, Francisco; Santos, Nuno; Van Ranst, Marc; et al.
Abstract: Animal host–microbe interactions are a relevant concern for wildlife conservation, particularly regarding generalist pathogens, where domestic host species can play a role in the transmission of infectious agents, such as viruses, to wild animals. Knowledge on viral circulation in wild host species is still scarce and can be improved by the recent advent of modern molecular approaches. We aimed to characterize the fecal virome and identify viruses of potential conservation relevance of diarrheic free‐ranging wolves and sympatric domestic dogs from Central Portugal, where a small and threatened wolf population persists in a highly anthropogenically modified landscape. Using viral metagenomics, we screened diarrheic stools collected from wolves ( n = 8), feral dogs ( n = 4), and pet dogs ( n = 6), all collected within wolf range. We detected novel highly divergent viruses as well as known viral pathogens with established effects on population dynamics, including canine distemper virus, a novel bocavirus, and canine minute virus. Furthermore, we performed a 4‐year survey for the six wolf packs comprising this endangered wolf population, screening 93 fecal samples from 36 genetically identified wolves for canine distemper virus and the novel bocavirus, previously identified using our metagenomics approach. Our novel approach using metagenomics for viral screening in noninvasive samples of wolves and dogs has profound implications on the knowledge of both virology and wildlife diseases, establishing a complementary tool to traditional screening methods for the conservation of threatened species. Abstract : In diarrheic stools collected from wolves ( n = 8), feral dogs ( n = 4), and pet dogs ( n = 6), all collected within wolf range, we detected novel highly divergent viruses as well as known viral pathogens with established population dynamics effects, including canine distemper virus, a novel bocavirus, and canine minute virus. Furthermore, we surveyed all six wolf packs comprising this endangered wolf population, screening 95 fecal samples from 37 genetically identified wolves for canine distemper virus and a bocavirus, which were previously identified using our metagenomics approach. Wolf photo credits to Artur Oliveira (Centro de Recuperação do Lobo Ibérico).